Feasibility of fine needle aspiration for diagnosis of b-cell lymphoma of the thyroid: a case series and review of the literature - Alexander D. Karabachev; William J. Brundage; Mirabelle B. Sajisevi; Allison L. Ciolino (Diagnostic Pathology, 2023)
Abstract Background Primary thyroid lymphoma (PTL) is a rare cancer accounting for approximately 5% of thyroid malignancies. Historically, incisional biopsy has been the gold standard for definitive diagnosis of PTL, however, the use of cell block as an adjunct to fine needle aspiration (FNA) provides a high sensitivity and specificity for diagnosis and classification. Methods Three patients presented with a symptomatic enlarging thyroid mass. Patient 1 underwent incisional biopsy under general anesthesia, Patient 2 underwent core needle biopsy to avoid high risk intubation, and Patient 3 underwent fine needle aspiration alone with the use of cell block. Results All patients were diagnosed with a fully classified non-Hodgkin’s lymphoma using immunohistochemistry, flow cytometry, and fluorescence in situ hybridization (FISH) analysis. Conclusions FNA for diagnosis of some subtypes of PTL is feasible and preferred in cases that are particularly high risk for general anesthesia. This minimally invasive technique is safe and cost effective as it avoids expenses associated with operative intervention.